MODIFICATION OF CARBON PASTE ELECTRODE WITH MOLECULARLY IMPRINTED POLY(METHYL ORANGE) FOR VOLTAMMETRIC DETERMINATION OF URIC ACID - Annisa Aulia, Mega
Uric acid is the main end product of purine metabolism in the body. In humans, uric acid is produced both from the digestion of foods containing purines and purine nucleotide synthesis. Generally, these compounds are found in body fluids, such as serum, blood, and urine, and most are released from the body by the kidneys through urinary excretion. In healthy conditions, serum uric acid concentrations range from 0.2 – 0.5 mM, while urinary excretion ranges from 1.4 – 4.4 mM. The level of uric acid concentration in the body that is above the normal range indicates symptoms of several diseases, such as arthritis, hyperuricemia, and pneumonia. In this study, a voltammetric method for uric acid determination has been successfully developed using carbon paste electrode modified with molecularly imprinted polymer layers. The modification process was carried out by electropolymerization using methyl orange as a monomer and uric acid as a template analyte. Uric acid was determined using differential pulse voltammetry (DPV) technique in PBS 0.1 M pH 7 0.1 M in the potential range of -0.2 – 0.8 V with a scan rate of 10 mV/s. The measurement results of the modified carbon paste electrode have good repeatability, linear work range at concentrations of 1 - 100 µM, and limit of detection of 0.93 µM. The electron transfer process is controlled by the diffusion process. Determination of uric acid samples in urine showed percent recovery of 92.85 – 98.77 %.